Revealing the buried past geophysics for archaeologists - Gaffney, Christopher F.; Gater, John (The History Press, 2010)
'Revealing The Buried Past' examines the increasingly sophisticated technology that enables archaeologists to identify much that is beneath the soil and so reduce the amount of excavation that is needed.